PENERAPAN MODEL PEMBELAJARAN THE POWER OF TWO UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS V SD NEGERI 56 KOTA TERNATE PADA TEMA 6 SUBTEMA 2 PERPINDAHAN KALOR DI SEKITAR KITA - Neli Yusliana Agus; Kodrat Hi Karim; Eko Purnomo (PEDAGOGIK, 2023)
The purpose of this study is to express the learning model of The Power Of Two in grade V students of SD Negeri 56 Ternate City, after using the learning model The Power Of Two in Theme 6 Subtheme 2 Heat Transfer Around Us. This research is Classroom Action Research (CAR). The subjects of the study were class V students with a total of 26 students consisting of 9 men and 17 women. Data collection techniques in this study are observation, documentation and tests. Data analysis techniques in this study were carried out in three stages, namely to determine individual student learning outcomes, to determine the completeness of student learning classically and to calculate the percentage of student and teacher activity results.The results of this study were 2 cycles, where cycle I obtained learning completeness with a percentage of 42.30% as many as 11 students, student activity 65.27% and teacher activity 68.75%. Then in the second cycle, student learning completeness was obtained with 96.15% as many as 25 students, student activity 90.27% and teacher activity 93.75%. Based on the results of the percentage above, it can be concluded that Learning Using The Power Of Two Model In Learning Theme 6 Subtheme 2 Heat Transfer Around Us can improve the learning outcomes of grade V students of SD Negeri 56 Ternate City.